Insect pests and diseases of Lai Chau ginseng (Panax vietnamensis var. fuscidiscus K. Komatsu, S. Zhu & S.Q. Cai) - Hien Thuy Phan, My Thi Chu*, Ha Thi Dang; Binh Thi Nguyen; Tien Tran Minh; Hien Nguyen; Stephen Harper (Vietnam Journal of Science, Technology and Engineering, 2026)
Panax vietnamensis var. fuscidiscus, commonly known as Lai Chau ginseng, is a high-value medicinal plant native to the mountainous regions of northern Vietnam. To develop effective management strategies for Lai Chau ginseng, this research aimed to comprehensively assess the pests and diseases affecting its cultivation. In 2024, a survey was conducted in Sin Ho, Lai Chau province. A total of 48 symptomatic plant samples were collected and evaluated based on morphological characteristics and visible symptoms. Four major symptom groups were identified: insect-induced leaf damage (32%), damping off (29%), leaf spots (20%), and root rot and wilting. Two key insect pests were identified: Chinavia hilaris (green stink bug) and Pseudococcus citri (mealybug), which caused significant damage to flowers, fruits, and petioles. Additionally, five pathogens were identified, including Cladosporium paeoniae (leaf spot), Puccinia sp. (rust), and three soil-borne fungi (Fusarium solani, Pythium ultimum, and Rhizoctonia solani), responsible for root rot and damping-off. These findings provide important baseline data for developing Integrated Pest Management (IPM) strategies to support the sustainable cultivation of Lai Chau ginseng.